EVALUATION OF THE IMPACT OF IMPLEMENTING A CENTRALIZED LIBRARY MANAGEMENT SYSTEM - Indrawan, Irjus; Ekhwan, Syaiful; al-Sufi, Zahra; Bakhari, Zakhar (International Journal of Business and Information Technology, 2024)
The introduction of centralized library management systems has become an important trend in managing information resources in an efficient and integrated manner. The aim of this research is to evaluate the impact of implementing a centralized library management system on service quality, operational efficiency and user satisfaction. The research method used is a library research method targeting readers and librarians from various educational institutions. In addition, a qualitative approach was used through in-depth interviews to gain a more comprehensive understanding of implementation challenges. The research results show that a centralized library management system can increase the efficiency of collection management, facilitate user access to information, and significantly increase user satisfaction. However, several challenges were also identified, including the need for more intensive training for employees, high initial investment, and resistance to change.